Academic integrity and the University Library’s role in the doctoral education. - Østvand, Lene; Andreassen, Helene N. (UiT The Arctic University of Norway, 2017)
Presentation at Librarians' Information Literacy Annual Conference (LILAC), Swansea University, 10.-12. April 2017 Researchers meet an increasing amount of incentives that may lead to scientific misconduct (Edwards & Roy, 2017). A “publish or perish” culture is currently ruling, and quantity is emphasized over quality. Growth in the number of PhD students may lead to growth in competition for grants, future positions and the supervisors’ time. Simultaneously, the PhD students are expected to follow the norms of research ethics and produce high quality research. They thus meet the challenge of balancing the roles as “good scientists” and “good academics” (Carter, 2015). At the University Library in Tromsø (Norway), we have recently addressed the PhD students’ need for guidance on using and producing sources. In 2015, we launched the cross-disciplinary seminar series Take control of your PhD journey ( https://uit.no/ub/laringsstotte#linje2 ), where the traditional scope of information literacy has been widened to include the ethics of open science. During the seminars, we focus on discussions and learning activities, to stimulate reflection among the PhD students. We have also collected information on the PhD students’ thoughts on academic integrity and open science through open-ended questionnaires. We have learned that PhD students need a lot of guidance when it comes to open science, and especially open data. Many express positive surprise when it comes to the expertise present in the libraries. We therefore believe that the library needs to identify the role it can play in PhD support, and that the PhD students themselves should be made aware of what the library can offer. In this presentation, we will report on the attitudes our PhD students display towards academic integrity and open science. In light of these findings, we discuss the further development of information literacy teaching at higher academic levels. Future plans include formally integrating the seminar series as a part of the PhD course ...